Exploring self‐management in adult sickle cell disease patients' at a Teaching Hospital in Ghana - Ninon P. Amertil; Elikem Keli Ayitey; Doris Grace Kpongboe; Priscilla Y. A. Attafuah (Wiley, 2021)
Abstract Aim To evaluate the relationships among self‐efficacy, uncertainty, self‐management and emergency hospital visits yearly among adult sickle cell disease patients' and related demographics at a Teaching Hospital in Ghana. Design A quantitative cross‐sectional design. Method A purposive and convenience sample of 85 adult clients from a sickle cell clinic in Ghana completed research instruments. Data collection occurred in March and April 2019. Instruments used were the self‐efficacy scale, self‐care agency scale, Mishel uncertainty scale and socio‐demographic variables. Pearson correlation and regression techniques were used for analysis. Findings The correlation results showed a low positive and significant correlation between self‐efficacy and self‐management (r = 0.357, p < .01), a significant moderate negative relationship between self‐efficacy and uncertainty (r = −0.459, p < .01) and a significant low negative relationship between self‐management and uncertainty. For the regression, employment (p = .003) and marital status (p = .002) significantly predicted self‐management among others. Conclusion Self‐efficacy had positive and significant relationship with self‐management. Similarly, patients with family support and employment experienced better self‐management. Furthermore, patients with higher education and living with family had reduced illness uncertainty. Thus, the findings can improve self‐care measures and mitigate illness uncertainty for better health outcomes.